2009
DOI: 10.1016/j.mce.2009.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Anosmin-1a is required for fasciculation and terminal targeting of olfactory sensory neuron axons in the zebrafish olfactory system

Abstract: 1a is required for fasciculation and terminal targeting of olfactory sensory neuron axons in the zebrafish olfactory system. Molecular and Cellular Endocrinology, Elsevier, 2009, 312 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
3
22
0
1
Order By: Relevance
“…This targeted axonal migration is dependent on the presence of pioneer axons (Whitlock and Westerfield, 1998), which require functional Slit/Robo2 and chemokine signaling (Miyasaka et al, 2007) to fasciculate properly and extend into the OB primordia. Compromising the expression of Slit/Robo and other guidance molecules, such as anosmin-1 and netrin/DCC (Yanicostas et al, 2009;Madelaine et al, 2011;Lakhina et al, 2012), perturbs OSN axon targeting and leads to the formation of disorganized and incomplete glomerular arrays. Interestingly, the Robo2 mutant astray (Miyasaka et al, 2005) appears to display more severe developmental deficits in some glomeruli (lG 4 ) than in Figure 7.…”
Section: Early Development Of Glomerulimentioning
confidence: 99%
See 2 more Smart Citations
“…This targeted axonal migration is dependent on the presence of pioneer axons (Whitlock and Westerfield, 1998), which require functional Slit/Robo2 and chemokine signaling (Miyasaka et al, 2007) to fasciculate properly and extend into the OB primordia. Compromising the expression of Slit/Robo and other guidance molecules, such as anosmin-1 and netrin/DCC (Yanicostas et al, 2009;Madelaine et al, 2011;Lakhina et al, 2012), perturbs OSN axon targeting and leads to the formation of disorganized and incomplete glomerular arrays. Interestingly, the Robo2 mutant astray (Miyasaka et al, 2005) appears to display more severe developmental deficits in some glomeruli (lG 4 ) than in Figure 7.…”
Section: Early Development Of Glomerulimentioning
confidence: 99%
“…Such analyses might be complicated by large increases in OSN numbers, but it is also possible that new glomeruli form de novo from new populations of OSN axons. This possibility may be addressed with zebrafish that permit visualization of individual OSN axon types (Lakhina et al, 2012), and similar strategies have already proven valuable in studying rodent OB development (Potter et al, 2001;Feinstein and Mombaerts, 2004;Zou et al, 2004). To summarize, the zebrafish glomerular map develops in two stages: (1) a coarse positional map that includes early emerging large glomeruli forms during embryonic development; and (2) this coarse map is progressively refined during 5 weeks of larval development to produce an array of discrete glomeruli that closely resemble their adult counterparts in number and distribution.…”
Section: Distinct Modes Of Glomerular Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergman, Bocca, et al (2011a) showed that olfaction and spontaneous onset of puberty are correlated in CHARGE syndrome: all (11/11) patients with hypogonadotropic hypogonadism (HH) were unable to smell, whereas patients without HH had the ability to smell (4/4). This combination of symptoms is also seen in Kallmann syndrome and is explained by common factors that facilitate axon guidance for both olfactory and GnRH neurons (Yanicostas, Herbomel, Dipietromaria, & Soussi‐Yanicostas, 2009). The correlation of anosmia and HH enables prediction of HH in patients with CHARGE experiencing anosmia, which is useful because after the age of 3 months endocrinological assessment of HH is impossible until the onset of puberty.…”
Section: Value Of Cranial Imaging In Treatment and Managementmentioning
confidence: 95%
“…A anosmina-1 é formada por uma região rica em cisteína, um domínio WAP ("whey acidic protein") e quatro repetições de fibronectina tipo III (FNIII), estruturalmente relacionadas às moléculas de adesão celular, e várias regiões de ligação a proteoglicanas sulfato de heparina (27,28). Diferentes estudos in vitro têm demonstrado que a anosmina-1 é capaz de controlar inúmeras funções celulares, incluindo alongamento de axônios e fasciculação, morfogê-nese epitelial e atividade migratória de neurônios liberadores de GnRH (31)(32)(33)(34)(35). É interessante notar que, apesar de demonstrada a existência da anosmina-1 em camundongos, o ortólogo do gene KAL1 ainda não foi identificado em roedores (34).…”
Section: Gene Kal1unclassified